THREE NEW RECORDS OF SCARABAEINAE (SUBFAMILY: SCARABAEINAE; FAMILY: SCARABAEIDAE; ORDER: COLEOPTERA) FROM THE ARID ZONE OF SOUTH PUNJAB, PAKISTAN - Muhammad Waseem; Santosh Kumar; Riffat Sultana; Irfan Baboo; Zahid Manzoor (Journal of Animal and Plant Sciences, 2026)
The Cholistan Desert in South Punjab, Pakistan, represents a historically under-surveyed arid ecosystem where the insect fauna, particularly dung beetles (Scarabaeidae: Scarabaeinae), remains poorly documented. Given the crucial ecological services provided by dung beetles, including nutrient cycling, soil aeration, and pest control, understanding their diversity is essential for appreciating the functioning and health of desert ecosystems. This study addresses this knowledge gap by surveying the Scarabaeinae fauna of this region. A total of 123 specimens were collected from the Cholistan Desert and identified as belonging to two genera: Onitis Fabricius, 1798 and Digitonthophagus Balthasar, 1959. The species include Onitis philemon Fabricius, 1801, Digitonthophagus uks Génier, 2017, and Digitonthophagus catta Fabricius, 1787, This study documents all of these species for the first time in this arid zone. This discovery enhances the known biodiversity of the region. It underscores the ecological value of scarab beetles in Pakistan's desert ecosystems, highlighting the importance of further entomological research to inform conservation efforts.
Keywords: Beetles; Biodiversity; Cholistan desert; Regional record; Scarabaeinae; Systematics